Distribution of Kainate Receptor Subunits at Hippocampal Mossy Fiber Synapses - Darstein, Melanie (J Neurosci, 2003)
Kainate receptors function as mediators of postsynaptic currents and as presynaptic modulators of synaptic transmission at mossy fiber synapses. Despite intense research into the physiological properties of mossy fiber kainate receptors, their subunit composition in the presynaptic and postsynaptic compartments is unclear. Here we describe the distribution of kainate receptor subunits in mossy fiber synapses using subunit-selective antibodies and knock-out mice. We provide morphological evidence for the presynaptic localization of KA1 and KA2 receptor subunits at mossy fiber synapses. Immunogold staining for KA1 and KA2 was commonly seen at synaptic contacts and in vesicular structures. Postsynaptic labeling in dendritic spines was also observed. Although KA1 predominantly showed presynaptic localization, KA2 was concentrated to a greater degree on postsynaptic membranes. Both subunits coimmunoprecipitated from hippocampal membrane extracts with GluR6 but not GluR7 subunits. These results demonstrate that KA1 and KA2 subunits are localized presynaptically and postsynaptically at mossy fiber synapses where they most likely coassemble with GluR6 subunits to form functional heteromeric kainate receptor complexes.